The Association of Serum Hepcidin Levels and Insulin Resistance in PCOS Patients: A Case-Control Study - Batool Hossein Rashidi; Soheila Shams; Mamak Shariat; Maryam Bagheri; Marziyeh Mohebi; Fedyeh Haghollahi (Tehran University of Medical Sciences, 2019)
Objective: To investigate the relationship between insulin resistance and hepcidin levels in patients with PCOS. Materials and methods: In this case-control study fifty- six patients with PCOS and forty - one healthy control subjects were included. Plasma levels of hepcidin, IL-6, Serum Insulin and ferritin using ELISA method, serum iron levels using a spectrophotometric method, and Insulin resistance by using HOMA  were measured in the two groups of PCOS (case group) and  healthy subjects (control group). The results were analyzed by student's t-test, General Linear Model, Binary logistic and linear regression tests. Results: The mean hepcidin level was 1.97 ± 0.53 pg/ml and 2.40 ± 0.25pg/ml in the case and control groups, respectively. The t-test results showed a significant difference between the two groups (p = 0.0001). The mean of insulin level in case and control group was 30.65 ± 15.02g/dl and 14.71 ± 10.46g/dl, respectively. The t-test analysis indicated a significant difference between the two groups (p = 0.0001). There was an inverse relationship between the level of hepcidin with HOMA-IR (β = -0.629, p = 0.04), and IL-6 (β = -0.243, p = 0.015) in both groups. The adjusted OR proved a statistically significant association between serum hepcidin (OR = 0.063; 95 % CI: 0.01-0.385, p-value  =  0. 003) and HOMA (OR  =  1.569; 95 % CI: 1.254-1.964, p-value  =  0.001) with PolycysticOvarian Syndrome. Conclusion: There was an inverse relationship between hepcidin levels and insulin resistance in both groups meaning decrease in hepcidin levels and increase in insulin resistance may increase the risk of PCOS.